Heat transfer and pressure drop characteristics in turbulent flow through a tube - Bhuiya, M.M.K.; Ahamed, Jamal Uddin; Sarkar, M.A.R.; Salam, B.; Masjuki, Haji Hassan; Kalam, M.A.; Saidur, Rahman; Sayem, A.S.M. (Taylor & Francis, 2012)
An experimental investigation has been carried out for turbulent flow through a tube with perforated strip inserts. Strips were of mild steels with circular holes of different diameters. Flow varies, with ranging Reynolds numbers from 15,000 to 47,000. Air velocity, tube wall temperatures, and pressure drops were measured for a plain and strip-inserted tube. The heat transfer coefficient and friction factor were found to be 2.80 times and 1.8 times, respectively, that of the plain tube. The heat transfer performance was evaluated and found to be 2.3 times that of the plain tube based on constant blower power.